Emotional Intelligence in Marketing: Connecting Brands with Consumers - Eko Tama Putra Saratian; Marwan Efendi; Miranti Pradipta Utami (SAFE-Network, 2024)
This study investigates the relationship between emotional intelligence, brand communication strategies, consumer brand perception, and customer loyalty within the context of PT. Lautan Luas Tbk. Through quantitative analysis utilizing Smart PLS, data was collected from a sample of 80 individuals using random sampling techniques. The results reveal significant direct effects of emotional intelligence and brand communication strategies on consumer brand perception and customer loyalty, as well as significant indirect effects of both emotional intelligence and brand communication strategies on customer loyalty through consumer brand perception. Specifically, higher levels of emotional intelligence among marketing staff and effective brand communication strategies positively influence consumer brand perception, subsequently leading to increased customer loyalty. These findings emphasize the importance of emotional intelligence and strategic brand communication in cultivating strong brand-consumer relationships and driving sustainable business growth.